Exposure to anti-smoking advertising across six European countries, findings from the international tobacco control six european countries (ITC-E6) survey of the EUREST-PLUS study - Sarah O Nogueira (Tobacco Prevention and Cessation, 2018)
Introduction Exposure to anti-smoking advertising and its effects differ across countries. This study examines: 1) reported exposure to anti-smoking advertising on traditional mass media and internet/social media; 2) the relationship between exposure to anti-smoking advertising and two other variables: knowledge of the harms of smoking/SHS and quit attempts in six European countries.